Iron homeostasis in inflammation: a single centre prospective observational study in medical inpatients (Swiss Medical Weekly, 2017)
AIMS OF THE STUDY: We aimed to assess a potential association of iron status with mortality and morbidity of inpatients with systemic inflammation. METHODS This was a single centre prospective observational study. From April 2014 to October 2014, all consecutive medical inpatients aged ≥18 years with a C-reactive protein value >5 mg/l on hospital admission were eligible for the study. We excluded pregnant women and patients with terminal renal insufficiency or past allogeneic stem cell transplantation. For all patients, a complete set of serum iron parameters was obtained on hospital admission. In the final analysis, the in-hospital all-cause mortality and several morbidity measures (length of stay, number of secondary diagnoses and Charlson Comorbidity Index) were compared between four distinct iron status groups: patients having iron deficiency anaemia, iron deficiency without anaemia, anaemia without iron deficiency, and normal iron status. Iron deficiency was quantifies as the serum transferrin receptor / ferritin index, with a cut-off level of 1.5. RESULTS A total of 438 patients were included in the final analysis. Patients with iron deficiency had a higher in-hospital mortality than patients with iron deficiency anaemia, anaemia without iron deficiency, or normal iron status (6% vs 1%, 5%, and 1%, respectively; p = 0.042). Patients with iron deficiency anaemia had a higher number of secondary diagnoses (mean 8.4; standard deviation 4.2) and a higher Charlson Comorbidity Index (mean 1.8; standard deviation 1.9) than patients with iron deficiency, anaemia without iron deficiency, or normal iron status (p